Chemical attributes of soils with eggshell application - Mantovani, José Ricardo; Ferreira, Matheus Esteves Rocha; Santos, Anderson Romão dos; Costa, Belchior de Souza; Florentino, Ligiane Aparecida (Científica, 2017)
Eggshell is an industrial residue which can be used as an acidity corrective, but its employment must follow some criteria. The objective of the present work was to evaluate the effect of eggshell on fertility attributes of soils with different clay contents. The experiment was conducted under laboratory conditions, from September to December 2015. A completely randomized design was used in a 2 x 6 factorial scheme, with two additional treatments and four replications, totaling 56 experimental units. The treatments were composed by the combination of two soils with different texture classes (sandy and clayey) and six doses (0, 1, 2, 3, 4 and 5 t ha-1) of eggshell, based on the volume of soil used. In the additional treatments, dolomitic limestone was used in each soil, instead of eggshell, aiming to raise their initial base saturation (V%) to 70%. Portions of 0.25 dm3 of each soil received the doses of eggshell or limestone, being then moistened to 70% of the water retention capacity and remaining in incubation for 60 days. After the incubation, the pH in CaCl2, the potential acidity (H+Al) and the soil contents of P, extracted by Mehlich, K+, Ca2+, Mg2+ e Al3+ were evaluated. Eggshell corrects the acidity and increases the Ca2+ and Mg2+ levels, especially in sandy soil, yet less efficiently than limestone.